Influence of Parity on Milk Production and Composition, Udder Morphology and Resumption of Ovarian Cyclicity in Postpartum Surti Buffaloes (Bubalus bubalis) - Sriranga, Karpenahalli Ranganatha; Rao, Thakur Krishna Shankar; Harini, Kallambella Ramakrishnegowda; Singh, Rana Ranjeet; Patel, Navin Babulal (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of the present study was to investigate the influence of parity on milk yield, udder biometry and health, and ovarian cyclicity in postpartum Surti buffaloes. Based on parity, fourteen Surti buffaloes were grouped as primiparous and multiparous. Milk yield was recorded on daily basis (up to 80 days) and milk samples were collected on the day of calving, 7th, 15th, 30th, 45th, 60th and 80th day post- calving for composition analysis and somatic cell count (SCC). Serum progesterone level was assayed on 0th, 15th, 30th and 60th day of calving. Higher milk yield was observed in multiparous animals, consistent with the higher udder biometrical parameters as compared to primiparous animals. Parity did not affect significantly the milk composition (milk protein, lactose and SNF), except for milk fat and total solids. Serum progesterone concentration was not influenced by parity. Overall SCC was higher in primiparous animals along with delayed initiation of ovarian cyclicity. From this study it could be conferred that parity significantly affects the milk productivity and reproductive performance in postpartum Surti buffaloes. Therefore, multiparous buffalo could be selected on farmer’s door step keeping in view its production, better udder health and fast resumption of ovarian cyclicity.